Licochalcone A: a review of its pharmacology activities and molecular mechanisms - Liu, Meihua; Du, Yang; Gao, Dejiang (Frontiers in Pharmacology, 2024)
Licorice, derived from the root of Glycyrrhiza uralensis Fisch, is a key Traditional Chinese Medicine known for its detoxifying, spleen-nourishing, and qi-replenishing properties. Licochalcone A (Lico A), a significant component of licorice, has garnered interest due to its molecular versatility and receptor-binding affinity. This review explores the specific roles of Lico A in various diseases, providing new insights into its characteristics and guiding the rational use of licorice. Comprehensive literature searches using terms such as "licorice application" and "pharmacological activity of Lico A" were conducted across databases including CNKI, PubMed, and Google Scholar to gather relevant studies on Lico A's pharmacological activities and mechanisms. Lico A, a representative chalcone in licorice, targets specific mechanisms in anti-cancer and anti-inflammatory activities. It also plays a role in post-transcriptional regulation. This review delineates the similarities and differences in the anti-cancer and anti-inflammatory mechanisms of Lico A, concluding that its effects on non-coding RNA through post-transcriptional mechanisms deserve further exploration.Flavonoids, common in nature (Perezvizcaino and Fraga, 2018), typically form glycosides in plants or exist in their free form (Vukics and Guttman, 2008). This structural diversity translates to varied pharmacological activities, including free radical scavenging, especially in flavonoids with catechol structures (Mukne et al.